2008
DOI: 10.1007/s12052-008-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

Charting Evolution’s Trajectory: Using Molluscan Eye Diversity to Understand Parallel and Convergent Evolution

Abstract: For over 100 years, molluscan eyes have been used as an example of convergent evolution and, more recently, as a textbook example of stepwise evolution of a complex lens eye via natural selection. Yet, little is known about the underlying mechanisms that create the eye and generate different morphologies. Assessing molluscan eye diversity and understanding how this diversity came about will be important to developing meaningful interpretations of evolutionary processes. This paper provides an introduction to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 52 publications
(57 reference statements)
0
55
0
1
Order By: Relevance
“…However, studies based on molecular biology and evolution have revealed that, even though the evolutionary processes of different types of eyes seem different, the molecular basis is shared among the various eye types and they arose by divergent evolution (Nilsson 2004;Serb and Eernisse 2008). These phenomena have often been explained by the concepts of convergent and divergent evolution.…”
Section: Diversification Of the Eyementioning
confidence: 99%
“…However, studies based on molecular biology and evolution have revealed that, even though the evolutionary processes of different types of eyes seem different, the molecular basis is shared among the various eye types and they arose by divergent evolution (Nilsson 2004;Serb and Eernisse 2008). These phenomena have often been explained by the concepts of convergent and divergent evolution.…”
Section: Diversification Of the Eyementioning
confidence: 99%
“…A detailed account of the orientation, patterning, and cellular structure of the externally pigmented eye is provided by Boyle (1969aBoyle ( , 1977. Reviews on chiton sensory organs can be found in Charles (1966), Boyle (1977), Messenger (1981), Kaas and van Belle (1985), and Serb and Eernisse (2008).…”
Section: Polyplacophoramentioning
confidence: 99%
“…Coleolid cephalopods have rhabdomeric (microvillous) photoreceptors in a camera-type eye that optically functions in a similar manner to the vertebrate eye, making the cephalopod eye a famous example of convergent evolution (Packard 1972; however, see Serb and Eernisse (2008) and references within for alternative views). Specifically, the cephalopod eye resembles an all-rod elasmobranch eye with similar optics, speed, sensitivity, and resolution (Packard 1972).…”
Section: Cephalopodamentioning
confidence: 99%
“…Parallel evolution (e.g., Serb and Eernisse 2008) can be defined as the independent evolution of similar biological traits in at least two different lineages having similar phenotypic trajectories driven by common (developmental) constraints. Parallel evolution is often confused with convergence (Webb 1994) since both can result in taxa with highly similar characters, but the two concepts remain distinct (Serb and Eernisse 2008) even if there may be a continuum between parallelism and convergence (Gould 2002;Donoghue 2005).…”
Section: Introductionmentioning
confidence: 99%